Lactobacillus coryniformis subsp. coryniformis Strain Si3 Produces a Broad-Spectrum Proteinaceous Antifungal Compound - Magnusson, Jesper (American Society for Microbiology, 2001)
The antifungal activity spectrum of Lactobacillus coryniformis subsp. coryniformis strain Si3 was investigated. The strain had strong inhibitory activity in dual-culture agar plate assays against the molds Aspergillus fumigatus, A. nidulans, Penicillium roqueforti, Mucor hiemalis, Talaromyces flavus, Fusarium poae, F. graminearum, F. culmorum, and F. sporotrichoides. A weaker activity was observed against the yeasts Debaryomyces hansenii, Kluyveromyces marxianus, and Saccharomyces cerevisiae. The yeasts Rhodotorula glutinis, Sporobolomyces roseus, and Pichia anomala were not inhibited. In liquid culture the antifungal activity paralleled growth, with maximum mold inhibition early in the stationary growth phase, but with a rapid decline in antifungal activity after 48 h. The addition of ethanol to the growth medium prevented the decline and gave an increased antifungal activity. The activity was stable during heat treatment and was retained even after autoclaving at 121°C for 15 min. Maximum activity was observed at pH values of between 3.0 and 4.5, but it decreased rapidly when pH was adjusted to a level between 4.5 and 6.0 and was lost at higher pH values. The antifungal activity was fully regained after readjustment of the pH to the initial value (pH 3.6). The activity was irreversibly lost after treatment with proteolytic enzymes (proteinase K, trypsin, and pepsin). The antifungal activity was partially purified using ion-exchange chromatography and (NH(4))(2)SO(4) precipitation, followed by gel filtration chromatography. The active compound(s) was estimated to have a molecular mass of approximately 3 kDa. This is the first report of the production of a proteinaceous antifungal compound(s) from L. coryniformis subsp. coryniformis.